2022
DOI: 10.9734/arrb/2022/v37i130480
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Arsenic (As), Lead (Pb) and Chromium (Cr) Accumulation in Different Organs of Commercially Important Fish Species Collected from Chattogram Coastal Region of Bangladesh.

Abstract: Aims: The purpose of this study was to evaluate whether there are any significant toxic effects of the widely exposed metals on different organs (gill, liver, kidney, and muscle) of some commercially important marine fish species (Herpodon nehereus, Pampus chinensis and Hilsa ilisha). Study Design: The collection of the samples was done from January to March 2018 from Bay of Bengal near Chattogram city of Bangladesh. The study is based on randomly collected samples from the intended sampling sites (Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Among different organs, highest concentration of metals was observed in kidney tissues but the lowest concentration in muscles was found which is a positive finding as we mainly consume the muscles portion of fish widely. The concentration of heavy metals is recorded lowest in muscles compared to kidneys and livers in the commercially important marine fishes of Bangladesh [25] which is also found true for freshwater species in this study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Among different organs, highest concentration of metals was observed in kidney tissues but the lowest concentration in muscles was found which is a positive finding as we mainly consume the muscles portion of fish widely. The concentration of heavy metals is recorded lowest in muscles compared to kidneys and livers in the commercially important marine fishes of Bangladesh [25] which is also found true for freshwater species in this study.…”
Section: Discussionsupporting
confidence: 81%
“…al. [25] where they found that the Lead and Arsenic are accumulated in higher concentration in kidneys and livers of commercially important marine fishes in the Chattogram coast of Bangladesh. The metal concentrations in the gills of Rohu and Catla fish occurred in the decreasing order of Pb>As>Cr and As >Pb > Cr respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A parallel finding to this was illustrated in the study of Saha et al 57 who showed that high levels of various hazardous chemicals existed in fish feed. In contrast, Quader et al 71 found that the concentration of chromium in the fish feed sampled was not hazardous.…”
Section: Chromium Contamination In Fish Feedmentioning
confidence: 90%
“…chinensis and H . ilisha ) caught off Chattogram coast of Bay of Bengal, Quader et al 71 found that the concentration of arsenic was excessive, that is, higher than the WHO/FAO recommended level. Ahmed et al 62 gathered three fish samples ( Labeo rohita , Pangasius and Oreochromis mossambicus ) from 30 distinct agroecological zones of Bangladesh.…”
Section: Findings From Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation